2007
DOI: 10.1007/s00438-007-0208-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of gene expression profiles and identification of candidate genes involved in drought responses in Festuca mairei

Abstract: To understand the molecular genetic basis underlying drought tolerance in grasses, the cDNA-amplified fragment length polymorphism (cDNA-AFLP) technique was applied for identification of genes responding to drought stress in a xerophytic adapted plant, Festuca mairei. A total of 11,346 transcript derived fragments (TDFs) were detected, and 464 (4.1%) TDFs were identified as differentially expressed fragments (DEFs) during the drought treatment of the plant. The expression patterns of these DEFs included up-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 69 publications
2
16
1
Order By: Relevance
“…The expression of bZIP transcription factor and glyceraldehyde-3-phosphato-dehydrogenase was changed in water deficit-tolerant bean (Micheletto et al 2007) and sunflower plants (Roche et al 2007) as well as in maize exposed to high-salinity, cold and ABA (Zheng et al 2006). Aquaporins (Luu and Maurel 2005), kinase protein (Shou et al 2004), WRKY transcription factor (Marè et al 2004), and auxin-regulated protein (Wang and Bughrara 2007) were also described as responsive to water stress. This is consistent with our results and shows that the cDNA macroarray was an efficient method for identifying stress-regulated genes.…”
Section: Identification Of Differentially Expressed Genesmentioning
confidence: 96%
“…The expression of bZIP transcription factor and glyceraldehyde-3-phosphato-dehydrogenase was changed in water deficit-tolerant bean (Micheletto et al 2007) and sunflower plants (Roche et al 2007) as well as in maize exposed to high-salinity, cold and ABA (Zheng et al 2006). Aquaporins (Luu and Maurel 2005), kinase protein (Shou et al 2004), WRKY transcription factor (Marè et al 2004), and auxin-regulated protein (Wang and Bughrara 2007) were also described as responsive to water stress. This is consistent with our results and shows that the cDNA macroarray was an efficient method for identifying stress-regulated genes.…”
Section: Identification Of Differentially Expressed Genesmentioning
confidence: 96%
“…Traditionally, studies using cDNA-AFLP apply radioactively labeled primers or silver staining polyacrylamide gel for transcription profile analysis (Vos et al, 1995;Cracium et al, 2006;Wang and Bughrara, 2007;Zhang et al, 2010). According to Dresler-Nurmi et al (2000), fluorescence is an alternative to radioactive labeling since both methods provide comparable results.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that estimated future weather conditions will essentially affect physiological processes of plants in unforeseeable ways regarding isolated factors; though dependant on the interaction of growth strategy of the species and their capacity to adjust to the conditions of water availability in the soil. Other studies indicate that the effects of drought, salinity, temperature extremes and oxidative stress are interconnected and may induce similar damage on a cellular level, such as osmotic changes resulting in homeostasis interruption and ion distribution in the cell (Zhu, 2001;Wang et al, 2007). Accordingly, it is clear that abiotic stresses occur normally as a pool of factors which interact and that plants react to these environmental adversities in a complex manner (Shao et al, 2007).…”
Section: Water Deficitmentioning
confidence: 99%
“…It is a fact that some plants can tolerate stress events more efficiently than others. The Festuca mairei is a grass that can be used as reference in genomic studies to be compared to other grass due to its genetic adaptation to drought (Wang & Bughrara, 2007). Most of the genes repressed under drought stress in this grass are related to biogenesis and cellular metabolism whereas the induced genes are involved with transcription and defense (Wang & Bughrara, 2007).…”
Section: Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation